1998
DOI: 10.1002/(sici)1098-2302(199812)33:4<351::aid-dev6>3.3.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Body‐scaled ratio as a control parameter for prehension in 5‐ to 9‐year‐old children

Abstract: The purpose of the experiment was threefold: (a) To find evidence that grasping is body-scaled and thus remains invariant during development; (b) to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
26
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(32 citation statements)
references
References 18 publications
6
26
0
Order By: Relevance
“…Dynamical systems theory assumes that stable patterns of macroscopic behavior emerge and change over time due to the lawful nonlinear interaction of animal and environmental properties and components (Kelso, 1995;Kugler & Turvey, 1987;Turvey, 1990). In other words, rather than assuming that stable patterns of behav-ior are solely the result of mental or representational processes, researchers employing dynamical systems theory argue that the physical and informational constraints that exist between an individual and the environment operate to dynamically self-organize the observed patterns of human behavior (Kelso, 1995;Kugler, Kelso, & Turvey, 1980;van der Kamp & Davis, 1998).…”
Section: Affordances and Dynamical Systems Theorymentioning
confidence: 99%
“…Dynamical systems theory assumes that stable patterns of macroscopic behavior emerge and change over time due to the lawful nonlinear interaction of animal and environmental properties and components (Kelso, 1995;Kugler & Turvey, 1987;Turvey, 1990). In other words, rather than assuming that stable patterns of behav-ior are solely the result of mental or representational processes, researchers employing dynamical systems theory argue that the physical and informational constraints that exist between an individual and the environment operate to dynamically self-organize the observed patterns of human behavior (Kelso, 1995;Kugler, Kelso, & Turvey, 1980;van der Kamp & Davis, 1998).…”
Section: Affordances and Dynamical Systems Theorymentioning
confidence: 99%
“…Hence, it is quite likely that animals should evolve so as to perceive the action possibilities in their environments. And although it is hard to demonstrate empirically that affordances are the primary objects of perception, recent studies have revealed that humans are fairly accurate in perceiving what behavior the environment affords (e.g., Heft, 1993;Mark, 1987;Oudejans, Michaels, Bakker, & Dolne, 1996;Oudejans, Michaels, van Dort, & Frissen, 1996;van der Kamp, Savelsbergh, & Davis, 1998;Warren, 1984;Warren & Whang, 1987).…”
mentioning
confidence: 93%
“…Hysteresis has a long history in inanimate systems and has, in recent years, been variously reported in different animate systems. In particular it has been reported in a number of human perception-action experiments (e.g., Fitzpatrick, Carello, Schmidt, & Corey, 1994;Lopresti-Goodman, Richardson, Baron, Carello, & Marsh, 2009;Richardson, Marsh, & Baron, 2007;Tuller, Case, Ding, & Kelso, 1994;Van der Kamp, Savelsbergh, & Davis, 1998). Diedrich and Warren (1995) provided a dynamical systems account for human gait transition (with walking and running as two attractive states of the system) and demonstrated that gait transitions satisfy the criteria of nonlinear phase transitionsspecifically, they exhibit hysteresis, that is, higher transition speed for WR in a sequence of increasing treadmill speeds than for RW in a sequence of decreasing treadmill speeds.…”
Section: Introductionmentioning
confidence: 99%